2000
DOI: 10.1007/s11664-000-0161-x
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative analysis of small amounts of cubic GaN phase in GaN films grown on sapphire

Abstract: Thin GaN films, grown by metal organic chemical vapor deposition on the basal plane of sapphire substrates, were characterized by x-ray pole figures, highresolution x-ray diffraction and transmission electron microscopy. This combination was found sensitive to small amounts (down to 0.1%) of cubic GaN phase in specimens subjected to surface nitridation treatment prior to epitaxial growth. The presence of the cubic phase and its orientation relations to the hexagonal GaN matrix was established by means of pole … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2006
2006
2006
2006

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Significantly, no threading dislocations were observed in the nanowires, although (0001) basal-plane stacking faults were commonly observed. (0001) stacking faults are known to have a low defect energy and are frequently observed in GaN films [29][30][31][32][33] and have also been reported in GaN nanowires [9,12,13,34]. Figure 6 [0001] GaN direction and ∼16% in the [ 1100] GaN direction.…”
Section: Resultsmentioning
confidence: 96%
“…Significantly, no threading dislocations were observed in the nanowires, although (0001) basal-plane stacking faults were commonly observed. (0001) stacking faults are known to have a low defect energy and are frequently observed in GaN films [29][30][31][32][33] and have also been reported in GaN nanowires [9,12,13,34]. Figure 6 [0001] GaN direction and ∼16% in the [ 1100] GaN direction.…”
Section: Resultsmentioning
confidence: 96%
“…The structural characteristics of the aligned nanowires were investigated by transmission electron microscopy (TEM), which showed that the GaN nanowires have a single crystalline, wurtzite structure. The triangular sides of the [11][12][13][14][15][16][17][18][19][20] oriented nanowires were determined to consist of the (0001), (-1101), and (-110-1) planes, resulting in an isosceles cross-section. Significantly, no threading dislocations were observed in the nanowires, although (0001) basal-plane stacking faults were commonly observed.…”
Section: Nanowire Growth and Structural Characterizationmentioning
confidence: 99%
“…Significantly, no threading dislocations were observed in the nanowires, although (0001) basal-plane stacking faults were commonly observed. (0001) stacking faults are known to have a low defect energy and are frequently observed in GaN films [9][10][11][12][13] and have also been reported in GaN nanowires.…”
Section: Nanowire Growth and Structural Characterizationmentioning
confidence: 99%